The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s11130-005-9552-3
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharins of Black Gram (Vigna mungo L.) as Affected by Processing Methods

Abstract: The oligosaccharide content was determined in 12 different cultivars of black gram. The effect of various treatments such as soaking, cooking, and enzyme treatment on the raffinose family oligosaccharides of dry seeds and flour was studied. Ajugose, a higher oligosaccharide (DP 6) found in trace quantities in seeds, was shown in black gram by HPLC. The percent reduction of raffinose, stachyose, verbascose, and ajugose after soaking for 16 hr was 41.66%, 47.61%, 28.48%, and 26.82%, respectively in Local-I varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Soaking improves digestibility by leaching out many complex sugars from the beans that may otherwise cause flatulence. Girigowda et al (2005) have reported a considerable decrease in the amount of these sugars (raffinose, 41.7%, stachyose, 47.6%, verbascose, 28.5% and ajugose, 26.8%) in blackgram after soaking in water (bean:water, 1:10). Besides ratio, there are also other factors which can affect the RFO content in the beans during soaking.…”
Section: Influence Of Soakingmentioning
confidence: 99%
See 2 more Smart Citations
“…Soaking improves digestibility by leaching out many complex sugars from the beans that may otherwise cause flatulence. Girigowda et al (2005) have reported a considerable decrease in the amount of these sugars (raffinose, 41.7%, stachyose, 47.6%, verbascose, 28.5% and ajugose, 26.8%) in blackgram after soaking in water (bean:water, 1:10). Besides ratio, there are also other factors which can affect the RFO content in the beans during soaking.…”
Section: Influence Of Soakingmentioning
confidence: 99%
“…In mature legume seeds, RFOs are present at a level of 31e76% of the total soluble sugar content (Reddy, Pierson, Sathe, & Salunkhe, 1984). Blackgram contains 7.6, 6.5, 33.2 and 16.6 g/kg (dry wt basis) raffinose, stachyose, verbascose and ajugose, respectively (Girigowda, Prashanth, & Mulimani, 2005), while raw soybean (Glycine max (L.) Merr.) contains 19.2 and 43.2 g/kg (dry wt basis) raffinose and stachyose, respectively (Sarkar, Jones, Craven, & Somerset, 1997) and kidney bean (Phaseolus vulgaris L.) contains 2.9 and 18.4 g/kg (dry wt basis) raffinose and stachyose, respectively (Shimelis & Rakshit, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black gram is a rich protein food with protein content ranging from 26.0 to 28.4 % on a dry-weight basis. Proteins of black gram are easily digestible and very good sources of phosphoric acid and vitamins (Girigowda et al 2005). Like most other legume proteins, black gram proteins are deficient in sulfur-containing amino acids and are rich in lysine.…”
Section: Introductionmentioning
confidence: 99%
“…-Galactosidase has a number of biotechnological applications like production of sugar, processing of soymilk, conversion of blood type, and treatment of Fabry's disease. In the past few years, -galactosidase has been considered as eVective feed additive to remove non-digestible oligosaccharides, which occur in soybean meal-containing diet [7][8][9].…”
Section: Introductionmentioning
confidence: 99%